Moderasi Islamic Social Reporting pada Ukuran Perusahaan, Kecukupan Modal, dan Profitabilitas terhadap Nilai Perusahaan - Lely Diyas Asari; Supami Wahyu Setiyowati; Doni Wirshandono Yogivaria (Fakultas Ekonomi, UIN Maliki Malang, 2021)
The research objective determines whether the relationship between company size, capital adequacy and profitability on firm value was mediated by ISR at BUS in Indonesia period 2014-2019. The research method is a quantitative approach. The population used by BUS recorded OJK in 2014-2019. The sample used was 36 obtained from purposive sampling. The data analysis technique uses Path Analysis and the Patrial Least Square (PLS) analysis tool. The result of this research is that there is a direct effect on firm size, capital adequacy on firm value and ISR, except that capital adequacy has no effect on ISR, ISR influence on firm value. Indirectly, ISR mediate the influence of firm size, profitability, and not for capital adequacy on firm value